The Level of Attention to Life Skills in the Social Sciences Curriculum of Elementary School from the Perspective of Teachers in Sothern Iran - Tayebe Piri; Maryam Sahraei (Shiraz University of Medical Sciences, 2022)
Background: L ife s kills h elp t he i ndividuals i n d ifferent situations to communicate with others desirably and appropriately and to learn how to access social services, environment, and participation in life-making decisions and activities. The aim of this study was to investigate the level of attention to life skills in the social sciences curriculum of elementary schools from the perspective of teachers in Sothern Iran, Shiraz, in the academic year 2017-2018.Methods: In this descriptive-analytical cross-sectional study, we selected 315 fourth, fifth, and sixth grade primary school teachers in Shiraz by stratified random sampling method. A researchermade questionnaire with two dimensions of purpose and content of the curriculum with 26 questions was used. Subjects were asked to rate their views on each of the questions based on a five-point Likert scale. The results were analyzed through onesample t-test, independent t-test, and ANOVA analysis using SPSS22 software.Results: Based on the results, the educators believed that the level of attention to life skills in the goals and content of the curriculum was above average (P=0.001). Also, there was no significant difference between the views of male and female teachers on the level of attention to life skills in the social sciences curriculum in terms of objectives (P=0.793) and content (P=0.484).Conclusion: Since the main purpose of education is to help students adapt to different living environments, the development of applied life skills curricula is essential for all students.